Visitors' satisfaction with Cameron Highlands, Malaysia's popular tourist destination - Wan Mahamad, Wan Shahrul Aziah; Mohd Salim, Nor Zarina; A Tambi, Abdul Malek (2011)
Cameron Highlands is Malaysia's favorite retreat destination. It is located on the northwestern tip of the state of Pahang Malaysia's, some 200 kilometers north of Kuala Lumpur, Malaysia's capital city. The research is conducted for the purpose of evaluating Cameron Highland's attractiveness as a tourist destination. The customer (visitor) survey approach is chosen where visitors are asked to rate the merit of various tangibles they encounter in Cameron Highlands and their overall level of satisfaction with their visit. The survey is conducted because despite its popularity, Cameron Highlands's visitors are known to make complains concerning their tour experience such as physical developments that become eyesores to nature lovers, inadequate local transportation, lack of parking spaces (New Straits Times, 2009), and poor condition of public facilities, among others. Many visitors also raise concerns on the destruction of the highland's ecology, environment, and habitat relic due to extensive land-clearing activities for agricultural and physical developments (Mimi Syed Yusof, John and Shahrum Sayuthi, 2005; Ram, 2008; Singh, 2009). The importance of the research is it assesses the quality of facilities, products, services, and tour items in Cameron Highlands such as transportation, accommodation, food and beverages. Variation in attitudes, if any, between foreign and local visitors, people of different ages, genders, and professions, is examined using standard statistical methods Such analysis provides information to tourism industry actors to match tourism offers with different customer characteristics.